The role of phenolic OH groups of flavonoid compounds with H-bond formation ability to suppress amyloid mature fibrils by destabilizing β-sheet conformation of monomeric Aβ17-42. - Sahar Andarzi Gargari; Abolfazl Barzegar; Alireza Tarinejad (PLoS ONE)
Alzheimer's disease (AD) is a kind of brain disease that arises due to the aggregation and fibrillation of amyloid β-peptides (Aβ). The peptide Aβ17-42 forms U-shape protofilaments of amyloid mature fibrils by cross-β strands, detected in brain cells of individuals with AD. Targeting the structure of Aβ17-42 and destabilizing its β-strands by natural compounds could be effective in the treatment of AD patients. Therefore, the interaction features of monomeric U-shape Aβ17-42 with natural flavonoids including myricetin, morin and flavone at different mole ratios were comprehensively studied to recognize the mechanism of Aβ monomer instability using molecular dynamics (MD) simulations. We found that all flavonoids have tendency to interact and destabilize Aβ peptide structure with mole ratio-dependent effects. The interaction free energies of myricetin (with 6 OHs) and morin (with 5 OHs) were more negative compared to flavone, although the total binding energies of all flavonoids are favorable and negative. Myricetin, morin and flavone penetrated into the core of the Aβ17-42 and formed self-clusters of Aβ17-42-flavonoid complexes. Analysis of Aβ17-42-flavonoids interactions identified that the hydrophobic interactions related to SASA-dependent energy are weak in all complexes. However, the intermolecular H-bonds are a main binding factor for shifting U-shape rod-like state of Aβ17-42 to globular-like disordered state. Myricetin and morin polyphenols form H-bonds with both peptide's carbonyl and amine groups whereas flavone makes H-bonds only with amine substitution. As a result, polyphenols are more efficient in destabilizing β-sheet structures of peptide. Accordingly, the natural polyphenolic flavonoids are useful in forming stable Aβ17-42-flavonoid clusters to inhibit Aβ17-42 aggregation and these compounds could be an effective candidate for therapeutically targeting U-shape protofilaments' monomer in amyloid mature fibrils.